A comparative perspective: social support and life stress in working and non-working women: Social support and life stress in working and non-working women - Ferdowshi, Nafiza; Eti, Esmat Ara (Dhaka University Journal of Biological Sciences, 2026)
The purpose of this study was to explore potential differences in social support and life stress between working and non-working women. A total of 200 participants were recruited purposively from the Dhaka division. The Bangla version of the Perceived Stress Scale and the Bangla version of the Multidimensional Scale of Perceived Social Support were used as measuring instruments. This study used independent sample t-test as inferential statistics along with descriptive statistics (frequency, percentage, chi-square) for analyzing data. Analyses revealed a significant difference across social support and life stress in working versus non-working women. The study results indicated that working women experience more social support and life stress compared to non-working women. These findings provide a comparative understanding of social support and life stress indicating the urgency of tailoring community-based interventions for women. Therefore, the divergent perspectives of working and non-working women require to address in the context of Bangladesh. Dhaka Univ. J. Biol. Sci. 35(1): 95-105, 2026 (January)